Penggunaan Bahasa Indonesia dalam Keluarga Muda Etnis Bali - Tanjung Turaeni (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2006)
Abstract When people move from one city to the others, this and the new environment will influence the change and the use of language. By the use of survey method this article discusses how family who lives in Surabaya and the neighborhood employ the language for their daily life and activity. There has been rapid change in the use of the language for family internal communication among these Balinese. Different from Balinese family who live in Bali, the new balinese famili who lives in Surabaya prefers to use Indonesia language for communication among the families. They tend not to speak in Balinese language. Thus in this way Balinese language has been taken over by Indosian language. Key words: new environment, Balinese, family internal communication.